2020
DOI: 10.3389/fphys.2020.569915
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Continuous and Intermittent Blood Flow Restriction on Movement Velocity During Bench Press Exercise Against Different Loads

Abstract: This study evaluated the effects of continuous and intermittent blood flow restriction (BFR) with 70% of full arterial occlusion pressure on bar velocity during the bench press exercise against a wide range of resistive loads. Eleven strength-trained males (age: 23.5 ± 1.4 years; resistance training experience: 2.8 ± 0.8 years, maximal bench press strength – 1RM = 101.8 ± 13.9 kg; body mass = 79.8 ± 10.4 kg), performed three different testing protocols in random and counterbalanced order: without BFR (NO-BFR);… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 65 publications
2
33
4
Order By: Relevance
“…It is interesting to note that the increase of performance for ischemia condition was observed particularly in sets 3 to 5 (Figure 1), which suggests that ischemia allows the athletes to maintain a certain amount of force even in the presence of biochemical changes within the working muscle that lead to fatigue. Such an effect was also observed in the study of Wilk et al (2020b), which showed that both intermittent (used only during exercise) and continuous (used during exercise and during the rest interval) ischemia significantly increased peak bar velocity during the bench press exercise for lighter loads (20 to 50%1RM), while not for higher ones (60-90%1RM). Despite, the lack of an increase in bar velocity at higher loads during ischemia condition in study Wilk et al (2020b), the level of performance was maintained while, our research showed not only a maintenance of performance for the ischemia condition, but an increase in power output and bar velocity compared to control condition.…”
Section: Discussionsupporting
confidence: 67%
See 4 more Smart Citations
“…It is interesting to note that the increase of performance for ischemia condition was observed particularly in sets 3 to 5 (Figure 1), which suggests that ischemia allows the athletes to maintain a certain amount of force even in the presence of biochemical changes within the working muscle that lead to fatigue. Such an effect was also observed in the study of Wilk et al (2020b), which showed that both intermittent (used only during exercise) and continuous (used during exercise and during the rest interval) ischemia significantly increased peak bar velocity during the bench press exercise for lighter loads (20 to 50%1RM), while not for higher ones (60-90%1RM). Despite, the lack of an increase in bar velocity at higher loads during ischemia condition in study Wilk et al (2020b), the level of performance was maintained while, our research showed not only a maintenance of performance for the ischemia condition, but an increase in power output and bar velocity compared to control condition.…”
Section: Discussionsupporting
confidence: 67%
“…Such an effect was also observed in the study of Wilk et al (2020b), which showed that both intermittent (used only during exercise) and continuous (used during exercise and during the rest interval) ischemia significantly increased peak bar velocity during the bench press exercise for lighter loads (20 to 50%1RM), while not for higher ones (60-90%1RM). Despite, the lack of an increase in bar velocity at higher loads during ischemia condition in study Wilk et al (2020b), the level of performance was maintained while, our research showed not only a maintenance of performance for the ischemia condition, but an increase in power output and bar velocity compared to control condition. However, contrary to Wilk et al (2020b) in presented study the ischemia was used only during the rest intervals and not during the exercise, which suggests that different ischemia protocols may be an important factor in affecting on acute responses.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations